MEMAHAMI HAKIKAT DAN KARAKTERISTIK PEMBELAJARAN BIOLOGI DALAM UPAYA MENJAWAB TANTANGAN ABAD 21 SERTA OPTIMALISASI IMPLEMENTASI KURIKULUM 2013 - Suciati Sudarisman (UNIVERSITAS PGRI MADIUN, 2015)
Education in 21st century is very relevant to the purpose of education in Indonesia. Global era and the integration of technology in education, helped accelerate the synergy of knowledge across disciplines, thus giving birth to a new field. Learning aimed at creating an atmosphere of active, critical, analytical, and creative in solving problems through the development of thinking skills. Science (biology) essentially contains four elements are scientific processes, the product (scientific knowledge), attitudes (scientific attitudes), and technology. Processes in science implies manner or scientific activity for natural phenomena to describe the product obtained in the form of science facts, principles, laws, or theories. Science (biology) containing six elements are active learning, discovery / inquiry activity approach, scientific literacy, constructivism, science, technology, and society, and the existence of truth.There are two things that can be done by LPTK in optimizing the implementation of Curriculum 2013 are: 1) Strengthening understanding of the biology teacher candidates about the nature and characteristics of biology teaching; 2) Creating an academic situation so that prospective biology teachers have insight and knowledge about the importance of the role of science (biology) and as well as the direction of learning in the future. Learning aimed at creating an atmosphere of active, critical, analytical, and creative in solving problems using science process skills